2020
DOI: 10.1200/jco.2020.38.15_suppl.4520
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study assessing tolerability, efficacy, and biomarkers for durvalumab (D) ± tremelimumab (T) and gemcitabine/cisplatin (GemCis) in chemo-naïve advanced biliary tract cancer (aBTC).

Abstract: 4520 Background: In aBTC, GemCis is the standard of care as 1st-line treatment. Immunotherapies have shown early promising efficacy in some BTC patients (pts). We assessed D (anti-PD-L1) ± T (anti-CTLA-4) and GemCis in 1L BTC pts, including an extensive biomarker analysis (NCT03046862). Methods: Pts were first enrolled in the biomarker cohort (BMC) to receive 1 cycle of Gem 1000 mg/m2 + Cis 25 mg/m2 on D1 & D8, followed by GemCis + D 1120 mg and T 75 mg, Q3W until disease progression (PD). Subsequent pts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…Median DOR was 8.5 months and median OS was 10.1 months (95% CI: 6.2–11.4). Durvalumab and tremelimumab were also tested in combination with CISGEM in a phase 2 study that included 121 BTC patients in first-line, 45 treated with CISGEM and durvalumab and 46 with CISGEM, durvalumab and tremelimumab (30 patients also received this quadruplet therapy in a biomarker cohort) [ 62 ]. Median ORR was 50.0%, 73.3% and 73.4% in the biomarker, triplet and quadruplet cohort, respectively, with DCR of 96.7%, 100% and 97.8% and median DOR of 11.0, 9.8, and 9.1 months.…”
Section: Current Results Of Immune Therapies In Biliary Tract Cancmentioning
confidence: 99%
“…Median DOR was 8.5 months and median OS was 10.1 months (95% CI: 6.2–11.4). Durvalumab and tremelimumab were also tested in combination with CISGEM in a phase 2 study that included 121 BTC patients in first-line, 45 treated with CISGEM and durvalumab and 46 with CISGEM, durvalumab and tremelimumab (30 patients also received this quadruplet therapy in a biomarker cohort) [ 62 ]. Median ORR was 50.0%, 73.3% and 73.4% in the biomarker, triplet and quadruplet cohort, respectively, with DCR of 96.7%, 100% and 97.8% and median DOR of 11.0, 9.8, and 9.1 months.…”
Section: Current Results Of Immune Therapies In Biliary Tract Cancmentioning
confidence: 99%
“…PD-L1 expression after the first GemCis cycle, rather than baseline expression, trended with improved PFS. 32 Results from another recruiting study (NCT02834013) on dual ICIs combination after multiline therapies for advanced BTC are awaited. BTC is rather heterogeneous according to the different anatomical and molecular subtypes.…”
Section: M7824mentioning
confidence: 99%
“…With more extensive research, combined therapy has proven to be more efficient than monotherapy, and seems to be the future direction for this form of treatment. [28][29][30][31][32]34,[36][37][38][39][40][41] Nevertheless, the ideal combination partner, whether chemotherapy, molecular targeted therapy, or radiotherapy, needs to be evaluated, and which one is the best is still a matter of ongoing research. The proper dose, duration, and the sequence should be evaluated to obtain the maximum clinical benefits with limited toxicity.…”
mentioning
confidence: 99%
“…Triplet chemotherapy, such as GemCis plus nab-paclitaxel or S-1-irinotecan–oxaliplatin, have shown high response rates (40–50%) in single-arm studies, and these regimens may be as effective as neoadjuvant therapy [ 54 , 55 ]. A recent single-arm phase 2 study showed promising efficacy outcomes with durvalumab, anti-PD-L1 antibody, and GemCis for patients with unresectable or metastatic BTC, and this regimen is now under investigation (DEBATE: NCT04308174) as neoadjuvant therapy for resectable BTC ( Table 3 ) [ 56 ].…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%